PERAN GANDA IBU RUMAH TANGGA DALAM MENINGKATKAN EKONOMI KELUARGA DI DESA TAROHAN KECAMATAN BEO KABUPATEN KEPULAUAN TALAUD - Salaa, Jeiske (HOLISTIK, Journal Of Social and Culture, 2015)
In modern society, demands of this moment is increasing especially the field of social and economic. All this led to the status of women is no longer as a housewife course, but prosecuted role in various community social life, as often work helping husband, even to prop up family economy. Progress of the times often accompanied by the rise of the level of information and intellectual ability of human being. This joint the role of women in life continuously changed to answer the challenges of the times, no exception on the role of women in improving the welfare of family. Usually, the backbone of family life is a man or husband. But now the many women play an active role to support economic family. Women are not just into jewelry house but many also have a role in the family. In the desa Tarohan kecamatan Beo kabupaten Kepulauan Talaud the 280 people there are the women, fixed many are no it does not work. Those who work outside the house work as peddlers, employees, traders in the market, the canteen, maid households, a laundress clothes a total of 80 people housewives. Keywords : women, housewife, work